KETRAMPILAN PIJAT BAYI PADA PRIMIPARA DAN MULTIPARA - Etika Purnama Sari (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Primipara has more concern to fulfill baby's needs, one of which is baby massage. Multipara has more experience, but they are also faced with other demands. The behavior of mothers to do baby massage with the right technique is not much done. The purpose of this study is to analyze the skills of baby massage in primipara and multipara. The research design used is comparative analytics with the Cross Sectional approach. The population in this study were primipara and multipara. The sample in this study was 41 people, using a simple random sampling technique. The method of collecting data uses an observation sheet. The results showed the skills of multiparous baby massage with a good category (81%) while primipara as much (60%) in the bad category. The results of the chi square statistical analysis obtained a value of p = 0.018 and Î± = 0.05 where p <Î±, which means there is a difference between infant massage skills in primiparas and multiparas. Differences in primipara and multipara skills in baby massage techniques due to many factors including information, experience, and level of education. Primipara is expected to have more desire to massage her baby well and multiparas are expected to do baby massage more often. Keywords: baby massage, primipara, multipara